Prediction of the yielding behaviour of ductile porous materials through computational homogenization. Issue 2 (16th April 2018) - Pinto Carvalho, Rodrigo; Rodrigues Lopes, Igor A.; Andrade Pires, Francisco M.
Abstract : Purpose: The purpose of this paper is to predict the yield locus of porous ductile materials, evaluate the impact of void geometry and compare the computational results with existing analytical models. Design/methodology/approach: A computational homogenization strategy for the definition of the elasto-plastic transition is proposed. Representative volume elements (RVEs) containing single-centred ellipsoidal voids are analysed using three-dimensional finite element models under the geometrically non-linear hypothesis of finite strains. Yield curves are obtained by means of systematic analysis of RVEs considering different kinematical models: linear boundary displacements (upper bound), boundary displacement fluctuation periodicity and uniform boundary traction (lower bound). Findings: The influence of void geometry is captured and the reduction in the material strength is observed. Analytical models usually overestimate the impact of void geometry on the yield locus. Originality/value: This paper proposes an alternative criterion for porous ductile materials and assesses the accuracy of analytical models through the simulation of three-dimensional finite element models under geometrically non-linear hypothesis.